Artificially introduced aneuploid chromosomes assume a conserved position in colon cancer cells. - Kundan Sengupta; Madhvi B Upender; Linda Barenboim-Stapleton; Quang Tri Nguyen; Stephen M Wincovitch; Susan H Garfield; Michael J Difilippantonio; Thomas Ried (PLoS ONE)
Background Chromosomal aneuploidy is a defining feature of carcinomas. For instance, in colon cancer, an additional copy of Chromosome 7 is not only observed in early pre-malignant polyps, but is faithfully maintained throughout progression to metastasis. These copy number changes show a positive correlation with average transcript levels of resident genes. An independent line of research has also established that specific chromosomes occupy a well conserved 3D position within the interphase nucleus. Methodology/principal findings We investigated whether cancer-specific aneuploid chromosomes assume a 3D-position similar to that of its endogenous homologues, which would suggest a possible correlation with transcriptional activity. Using 3D-FISH and confocal laser scanning microscopy, we show that Chromosomes 7, 18, or 19 introduced via microcell-mediated chromosome transfer into the parental diploid colon cancer cell line DLD-1 maintain their conserved position in the interphase nucleus. Conclusions Our data is therefore consistent with the model that each chromosome has an associated zip code (possibly gene density) that determines its nuclear localization. Whether the nuclear localization determines or is determined by the transcriptional activity of resident genes has yet to be ascertained.